2023
DOI: 10.20525/ijrbs.v12i3.2483
|View full text |Cite
|
Sign up to set email alerts
|

Financial performance as mediation is influenced by diversification and intellectual capital on sustainability performance

Abstract: This study examines and analyzes diversification and intellectual capital on sustainability performance mediated by financial performance. This research was conducted at Sharia Commercial Banks (BUS) in Indonesia, registered with the Otoritas Jasa Keuangan (OJK) for 2011 - 2018, with a total sample of 10 Islamic banks that meet the criteria according to the sampling method used, namely purposive sampling. The data analysis technique used SEM-PLS with the help of WarpPLS 7.0 software. The results showed that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Banks support economic growth and state financial stability (Asma, 2018;Jeandry & Fajriyanti, 2023). In general, banks are financial institutions whose role is to collect funds from the public and then redistribute these funds through loans or credit schemes that can be given to companies or individuals (Duho & Onumah, 2019;Ovi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Banks support economic growth and state financial stability (Asma, 2018;Jeandry & Fajriyanti, 2023). In general, banks are financial institutions whose role is to collect funds from the public and then redistribute these funds through loans or credit schemes that can be given to companies or individuals (Duho & Onumah, 2019;Ovi et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, diversification cannot directly influence company performance, but can provide flexibility in capital formation because it can access resources, including external funding. Furthermore, Jeandry & Fajriyanti (2023) also revealed that intellectual capital and income diversification positively affect company performance. Moreover, income diversification can benefit companies with the company's flexibility to expand assets from various resources owned by the company.…”
Section: The Moderation Role Of Income Diversification On Intellectua...mentioning
confidence: 98%
See 3 more Smart Citations